2015
DOI: 10.1039/c5ra05545h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electricity generation and tetracycline removal in continuous flow electrosorption driven by microbial fuel cells

Abstract: A novel continuous flow electrosorption driven by microbial fuel cells (MFCs) was developed for the first time to remove tetracycline, the second most commonly used antibiotic, from synthetic wastewater. The MFC-sorption proved to be cost-effective without any external power consumption. Various operating parameters including pH, electrolyte concentration, initial concentration of tetracycline, number of MFCs connected in series and flow rate were investigated, and the adsorption kinetics of tetracycline remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…As mentioned above, in the case of DCF and NPX the observed insignificant but yet positive tendencies could be due to electrosorption to the positively charged electrode in in CW-BES. These OMPs are present in the form of charged ions or polar molecules and could therefore have been adsorbed after migrating to the system's electrode with opposite charge (Kong et al, 2013;Yang et al, 2015). Apart from that, MFCs seem to offer a beneficial environment for the growth of non-electrochemically active bacteria and increasing the metabolic rate of anaerobes due to the artificial presence of an insoluble electron acceptor, i.e.…”
Section: Naproxenmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, in the case of DCF and NPX the observed insignificant but yet positive tendencies could be due to electrosorption to the positively charged electrode in in CW-BES. These OMPs are present in the form of charged ions or polar molecules and could therefore have been adsorbed after migrating to the system's electrode with opposite charge (Kong et al, 2013;Yang et al, 2015). Apart from that, MFCs seem to offer a beneficial environment for the growth of non-electrochemically active bacteria and increasing the metabolic rate of anaerobes due to the artificial presence of an insoluble electron acceptor, i.e.…”
Section: Naproxenmentioning
confidence: 99%
“…However, in theory, electrosorption at the electrode with opposite charge (i.e. at the positively charged cathode, since DCF has a negative charge, see SI, Table S1) (Kong et al, 2013;Yang et al, 2015) could have resulted in an increased tendency for DCF removal (see Table 4 and SI, Figure S2b). Apart from that, CW-MFCs have been proven to enhance microbial activity (Hartl et al, 2019).…”
Section: Diclofenacmentioning
confidence: 99%
“…1 showed that the voltage outputs of MFC-VO were enhanced substantially with the increase of cathode potential in the presence of both V(V) and oxygen (from 498.4 AE 10.1 mV to 155.1 AE 18.5 mV during a typical cycle). Redox potentials of V(V) and oxygen based on Nernst equation were presented in eqn (5) and (6). Both V(V) and oxygen had relatively higher redox potentials, and were present together, leading to the higher voltage outputs of MFC-VO.…”
Section: Evaluation Of Power Outputsmentioning
confidence: 99%
“…[1][2][3] Thus, the MFC has been considered as a promising sustainable technology to meet increasing energy demands due to its simultaneous wastewater treatment and electricity generation. [4][5][6] In a typical MFC, electrons are produced in the anode chamber by catalysis of bacteria and then transferred to the cathode chamber through the external circuit where they are accepted by the electron acceptor. 7 Previous studies indicate that oxygen is the most widely used electron acceptor for MFC cathodes, owing to its inexhaustible supply and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…System. Reproduced with approval from references [34]. (F) 3D-BER: Three-dimensional biofilm electrode reactors.…”
Section: Introductionmentioning
confidence: 99%